Boards & bites : food styling and homemade recipes for elegant party planning - Francis, Melissa (Yellow Pear Press, 2022)
Learn the art of food styling with olives, grapes, cheese, jam, crackers, nuts and other treats with Melissa Francis' charcuterie board recipe book Boards and Bites.Be the hostess with the mostest! Learn the secrets of great food styling to elevate your charcuterie board creations. Boards and Bites is the perfect book for novice and experienced board creators alike. With accessible recipes and instructions, Melissa Francis shows readers how to create memorable spreads for every holiday party or festive occasion. Beautiful charcuterie spreads all in one place! Display your wine, fruits, nuts, jam, cheese, and bread in the most pleasing way. Boards and Bites is full of accessible recipes, board building basics, and food styling techniques. Get the behind-the-scenes story of how and why Francis creates her lovely charcuterie boards while you create your own divine bites with this charcuterie board recipe book. Inside, you'll find: Food styling techniques that will highlight you as the hostess of the year Step by step instructions on how to create beautiful charcuterie spreads Beautifully curated images of charcuterie boards with olives, grapes, cheese, and many other delicious treats.